Exchange Street, ca. 1928 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of Exchange Street. Several automobiles as well as pedestrians are included in the photograph. Copyprint 9 7/16 x 7 1/4, 9 13/16 x 7 5/8 overall Photographs